The Effectiveness of the Adaptability of the SIJIMAT BOSS Program in Increasing NIB Ownership Rates among MSMEs in Sukabumi City - Nuraeni, Syifa Zakiah; Purwanti, Dian; Basori, Yana Fajar FY (Peneliti.net, 2024)
This study examines the effectiveness of the SIJIMAT BOSS Program in increasing the number of Business Identification Number (NIB) ownership among MSMEs in Sukabumi City. The problem phenomenon identified is the low awareness of MSME actors of the importance of having NIB, even though NIB provides various benefits of legality and legal protection for businesses. This study aims to evaluate the extent to which the SIJIMAT BOSS program has succeeded in achieving the target of increasing NIB ownership and identifying inhibiting and supporting factors for the implementation of this program. The research method used is a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation using snowball sampling technique to determine informants. The results show that although this program has succeeded in increasing the number of NIB ownership, there are still some obstacles, such as the lack of effective socialization and cooperation between agencies that is not yet optimal. The program also shows good adaptation through cooperation with various parties, although it still needs improvement in several aspects, such as the provision of adequate facilities and infrastructure. In conclusion, the SIJIMAT BOSS Program has great potential in improving business legality among MSMEs, but still requires improvement in socialization and coordination between related agencies.